Planning of the Internal Audit of Supply Chain Management in Foreign Economic Activity: Theory and Practice (Internal Audit Planning) - Alexey Vladimirovich Petukh; Margarita Fridrihovna Safonova; Valentina Alekseevna Gribushenkova (International Journal of Supply Chain Management, 2020)
Abstract- Foreign economic activity and export operations in particular have a number of peculiarities, which significantly complicate the procedure for the accounting and distinguish them from the other business operations based on the supply chain. The existing legislative base for accounting and taxation does not provide unique regulations on the specifics of foreign trade contracts, pushing this responsibility down on economic entities. As a result, business processes of foreign economic activity may be reflected incorrectly in the accounting and analytical system. These reasons contribute to the complication of the procedures of audit evidence collection, the process of planning and documenting of the internal audit of foreign economic activity. The purpose of the study is to develop a methodology for internal audit planning and a concept of its strategy for export operations. As a result, the quality and reliability of the accounting [financial) statements should be improved. The results of monographic and regulatory analysis allowed us to determine the aspects of accounting that are at risk of data contamination. Using the methods of expert evaluation, information synthesis and supply chain strategy, the most optimal focus areas of audit program planning were determined. The present research introduces the author’s algorithm for internal audit planning, as well as the set of working documents to be implemented at this stage, i.e., internal control tests and audit plan. The audit plan, developed by the authors, includes the main directions of the internal audit of the export operations and contributes to a complex evaluation of the accounting accuracy. In addition, it optimizes significantly the verification process in terms of the labor costs and time expenditure. The author’s recommendations on planning and documenting can be applied for further development of theoretical and practical issues of the internal audit of foreign economic activity.